Covalent immobilization of alkaline proteinase on amino‐functionalized magnetic nanoparticles and application in soy protein hydrolysis. (8th December 2018) - Zhu, Xinjun; Li, Ying; Yang, Guang; Lv, Min; Zhang, Lianying
Abstract : Magnetic nanoparticles (MNPs) were synthesized and surface modified with (3‐Aminopropyl)triethoxysilane (APTES). The alkaline proteinase (AP) was covalently immobilized on the APTES‐modified MNPs through glutaraldehyde linkage. The resulting AP‐loaded MNPs have an average size of 84 nm in aqueous solution, and a magnetization of 40 emu/g, endowing the immobilized enzyme with excellent magnetic responsively and dispersity. The maximum amount of AP and catalytic activity immobilized 1.0 mg MNPs was 120 μg and 25.3 units, respectively. Immobilized AP showed maximum activity at pH 10.0 and 50°C. Compared with free enzyme, the immobilized AP exhibited better storage stability. Moreover, immobilized AP can be reused 10 times and still maintained about 50% of its initial activity. The degree of hydrolysis of soy protein hydrolysates for immobilized AP could reach 19.0%, which was closer to the value of free enzyme. The molecular weight (M.W.) analysis showed that the soy protein was hydrolyzed successfully into small peptides of two main fractions with an average M.W. of 742 and 2126 Da. This study indicated that the immobilized AP could be used to hydrolyze continuously soy protein for potential industry application. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2756, 2019.